Effect of ageing method, ageing period, cooking method and sample thickneá on beef textural characteristics - Panea, B.=700 1 Sañudo, C.; Olleta, J.L.; Civit, D.
(Es, En)
Ilus., 29 ref.
Keywords: PROPIEDADES REOLOGICAS; TEXTURA; CALIDAD; CARNE DE RES; PRENSADO; ESPAÑA; ANALISIS INSTRUMENTAL; COMPRESION WARNER-BRATZLER